2010
DOI: 10.1021/ic101060s
|View full text |Cite
|
Sign up to set email alerts
|

All-Nitrogen Coordinated Amidinato/Imido Complexes of Molybdenum and Tungsten: Syntheses and Characterization

Abstract: The first all-nitrogen coordinated bis(alkylamidinato)/bis(alkylimido) complexes of molybdenum and tungsten, [Mo(NtBu)(2){(iPrN)(2)CMe}(2)]and [W(NtBu)(2){(iPrN)(2)CMe}(2)], have been synthesized and fully characterized by (1)H and (13)C NMR spectroscopy, elemental analyses, high-resolution electron impact mass spectrometry, and Fourier transform infrared spectroscopy. Density functional theory calculations of the tungsten complex allow for geometry optimization and structural characterization by assignment of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
61
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(61 citation statements)
references
References 70 publications
0
61
0
Order By: Relevance
“…For example, bis(tert-butylimido)bis(dimethylamido)molybdenum(VI) (A) has been used as a precursor for the ALD of MoNx, [11,12] MoO3, [13,14] MoS2, [15][16][17] MoCxNy, [18,19] TiMoxNy, [20] and Al:MoS2. [21] N,N'-chelating ligands have also been used to prepare volatile bis(tert-butylimido)molybdenum(VI) compounds, such as amidinates (B), [22] pyrazolates (C), [10] guanidinates (D), [23] and diazabutadienyls (E). [24] However, only the amidinate B has been used for ALD to prepare MoO3 films with O3.…”
Section: Introductionmentioning
confidence: 99%
“…For example, bis(tert-butylimido)bis(dimethylamido)molybdenum(VI) (A) has been used as a precursor for the ALD of MoNx, [11,12] MoO3, [13,14] MoS2, [15][16][17] MoCxNy, [18,19] TiMoxNy, [20] and Al:MoS2. [21] N,N'-chelating ligands have also been used to prepare volatile bis(tert-butylimido)molybdenum(VI) compounds, such as amidinates (B), [22] pyrazolates (C), [10] guanidinates (D), [23] and diazabutadienyls (E). [24] However, only the amidinate B has been used for ALD to prepare MoO3 films with O3.…”
Section: Introductionmentioning
confidence: 99%
“…This requires development of new precursors of metal-organic nature and mild reaction by-products. As a result, several tungsten complexes of nitrogen-bound ligands (including amide, [17,18,33] imide, [18][19][20][21][22][23][24][25] hydrazido, [26,27] amidinate, [20] and guanidinate [28][29][30] ligands) as single-source precursors were developed. [31] These precursors afforded halogenand oxygen-free tungsten nitride or tungsten carbonitride films when used in the ALD/CVD process in the presence of appropriate reductive gases (H 2 or NH 3 ).…”
Section: Introductionmentioning
confidence: 99%
“…Amido–imido complexes of tungsten such as [W(N t Bu) 2 (NH t Bu) 2 ] and [Cl 4 (RCN)W(NR′)] (R = CH 3 , Ph; R′ = i Pr, C 3 H 5 , Ph) have been used as MOCVD precursors under single source precursor (SSP) conditions or in combination with NH 3 as reactive gas for the deposition of WN thin films. Earlier, we demonstrated that all nitrogen coordinated amidinato‐based tungsten complexes [W(N t Bu) 2 {( i PrN) 2 CMe} 2 ] and guanidinato‐based tungsten compounds like [W(N t Bu) 2 (NMe 2 ){( i PrN) 2 CNMe 2 }] and [W(N t Bu) 2 (H){( i PrN) 2 CNMe 2 }] can serve as potential precursor for the deposition of WN thin films in a home built CVD reactor .…”
Section: Introductionmentioning
confidence: 99%